MSMEs Business Empowerment Through Assistance in Analysing Cost of Goods Sold in Lengkong Karya, North Serpong District, South Tangerang - Riyani, Etik Ipda; Tantri, Sakina Nusarifa; Hardiana, Nadhira (PT Inovasi Pratama Internasional, 2025)
The COVID-19 pandemic in 2020 significantly impacted the performance of Micro, Small, and Medium Enterprises (MSMEs) in South Tangerang City, Banten, Indonesia. Despite a growing human population that suggests a potential boost to the local economy, MSMEs in Lengkong Karya Village, North Serpong District, are not fully capitalizing on these opportunities. According to the coordinator of economic development in Lengkong Karya Village, MSMEs in the area are grappling with capital issues, primarily due to their inability to accurately identify costs, particularly the Cost of Goods Sold (COGS). This challenge hinders their financial management, making it difficult to evaluate their performance. In response, the Community Service team aims to implement an assistance program focused on analyzing COGS for local MSMEs, with the purpose of enhancing their economic income and overall business performance. Utilizing a training and assistance method, the program will provide MSME owners with essential knowledge, skills, and practical guidance in financial management and cost analysis. This program results in an increase in understanding, skills, and experience in analyzing the Cost of Goods Sold among the MSMEs being operated. Ultimately, this initiative seeks to contribute to an increase in family economic income and foster sustainable growth within the local economy, allowing MSMEs to better leverage the opportunities available to them.